Immune Response of the Monocytic Cell Line THP-1 Against Six Aeromonas spp. - Fernández-Bravo, Ana; Figueras, Maria José (Frontiers in Immunology, 2022)
Aeromonas are autochthonous bacteria of aquatic environments that are considered to be emerging pathogens to humans, producing diarrhea, bacteremia, and wound infections. Genetic identification shows that 95.4% of the strains associated with clinical cases correspond to the species: Aeromonas caviae (37.26%), Aeromonas dhakensis (23.49%), Aeromonas veronii (21.54%), and Aeromonas hydrophila (13.07%). However, few studies have investigated the human immune response against some Aeromonas spp. such as A. hydrophila, A. salmonicida, and A. veronii. The present study aimed to increase the knowledge about the innate human immune response against six Aeromonas species, using, for the first time, an in vitro infection model with the monocytic human cell line THP-1 and to evaluate, the intracellular survival, the cell damage, and the expression of 11 immune-related genes (TLR4, TNF-α, CCL2, CCL20, JUN, RELA, BAX, TP53, CASP3, NLRP3, IL-1β). Transcriptional analysis showed an up-regulated expression of a variety of the monocytic immune-related genes, with a variable response depending upon the Aeromonas species. The species that produced the highest cell damage, independently of the strain origin, coincidentally induced a higher expression of immune-related genes and corresponded to the more prevalent clinical species A. dhakensis, A. veronii and A. caviae. Additionally, monocytic cells showed overexpression of the apoptotic and pyroptotic genes involved in cell death after A. dhakensis, A. caviae, and A. media infection. However, the apoptosis route seemed to be the only way of producing cell damage and death in the case of the species A. piscicola and A. jandaei, while A. veronii apparently only used the pyroptosis route.